Economics of a Single Currency - Sachdev, Harpreet Kaur (2007)
The last two decades saw a lot of changes in the world scenario, it includes not just the emergence of Euro but also a number of crises, namely in Mexico, Brazil, Russia and Southeast Asia. These two extremes pointed towards the fragility of the international financial system. As the world converges together via regional blocs, free trade areas, the need for a common currency has arisen. The increasing amount of literature in the area has propelled the need for a compilation. This review seeks to provide an overview of the ÃÂwhat-if probability for a common global currency. Beginning with an overview of the present International Monetary System, it ventures into the murky waters of the various contributions of economists towards the eventuality. The author tries to bring out the pros and cons of adopting a single currency, from an economic perspective, while testing the viability of the theory with the European Monetary Union, the only real example of an Economic and Monetary Union. The assessment aims to educate about the benefits and drawbacks of a single currency, leaving the reader to choose between the multi-currency world of today and the futuristic world of mono-money.